Leaving Cancer While Living with COVID-19: A Case Report - Jalil, Jasmin Bin; Kamarrudin, Siti Hajariah Binti; Bin Ishak, Kamal Rizal; Appalanaido, Gokula Kumar; Musa, Muhamad Yusri (International Journal of Human and Health Sciences (IJHHS), 2022)
Head and neck squamous cell carcinoma (HNSCC) is considered a category one priority in the radiotherapy treatment, therefore unscheduled interruption is to be kept as minimum as possible. Unexpected twists in clinical conditions necessitate proactive deviation from the standard of care practice which includes modifications of treatment scheduling and using the historical technique of treating pneumonitis with low dose radiation to the lung. This report described an experience in dealing with a gentleman diagnosed with early-stage tongue carcinoma undergoing curative brachytherapy treatment who developed acute postoperative febrile respiratory distress. His previous exposure to COVID-19 had complicated the initial diagnosis and management of his condition, amidst the rising COVID-19 pandemic in Penang, Malaysia. Rapid modification of the brachytherapy doses and schedules were arranged to ensure completion of radiotherapy before his clinical condition deteriorates. He was successfully treated for both conditions and managed to avoid mechanical ventilation. Living with COVID-19 significantly poses unknown conundrums which may require rapid assessment and multi-disciplinary input to reduce morbidity and mortality. A clear treatment goal shared by dedicated cancer treatment team members allows modifications tailored to the need and specific demand arising from the COVID-19 pandemic. The intended curative cancer therapies have to be balanced between other factors such as the morbidity of COVID-19 to the cancer patients, risks to health personnel, and the burden to the health care system during the pandemic crisis. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S20